Development Of Podio Models and Media (Poster Pop Up Touchless Button Audio) On Improving Dental Health Maintenance Behavior of Public Elementary School Students - Fatmasari, Diyah; Wahyuningtyas, Miranda Gita Wahyuningtyas; Suwondo, Ari; Sunarjo, Lanny; Daniati, Nia Daniati (Alta Dharma Publisher, 2022)
Introduction: The high prevalence of dental caries, of which is due to behaviors that can be overcome by the formation of dental health maintenance habits from an early age through PODIO models and media (poster pop up touchless button audio). Objective: Produce a PODIO (poster pop up touchless button audio) media model for improving dental health maintenance behavior in State Elementary School students. Method: This type of research using a mixed method is a combination of descriptive and analytical, with research and development (R&D) design, in model tests using a quasi-experiment design. Bivariate analysis using paired t-test. The number of respondents was 35 elementary school students. Result: The PODIO (poster pop up touchless button audio) model and media on improving the dental and oral health maintenance behavior of public elementary school students is feasible as a model for the health promotion of elementary school students. The PODIO (poster pop up touchless button audio) model and media effectively improved the knowledge, attitudes, and skills of public elementary school students towards the implementation of the model and media compared to the control group. Recommendation: The development of a feasible PODIO (poster pop up touchless button audio) model and media application and effectively improves the dental health maintenance behavior of public elementary school students so that it can be an alternative problem-solving in improving the dental health maintenance behavior of elementary school students. Keywords: pop up touchless button audio poster, dental health maintenance, dental health